Pharmacological activation of mGlu4 and mGlu7 receptors, by LSP2-9166, reduces ethanol consumption and relapse in rat. (1st May 2018) - Lebourgeois, Sophie; Vilpoux, Catherine; Jeanblanc, Jérôme; Acher, Francine; Marie, Nicolas; Noble, Florence; Naassila, Mickaël
Abstract: Addiction is a chronic and highly relapsing disorder hypothesized to be produced by an imbalance between excitatory and inhibitory neurotransmission. For more than a decade, emerging evidence indicates that manipulation of glutamatergic neurotransmission, by group III mGlu receptors (mGlu4/7/8), could be a promising approach to develop therapeutic agents for the treatment of addiction. Thus, the aim of the present study is to determine whether LSP2-9166, a mixed mGlu4/mGlu7 orthosteric agonist, could reduce ethanol self-administration, ethanol motivation and reacquisition after protracted abstinence in a preclinical model of excessive ethanol intake. Male Long Evans rats were chronically trained to consume large amount of ethanol in operant cages for several weeks. Once they reached a stable level of consumption (about 1 g of pure ethanol/kg bodyweight/15min), the effect of LSP2-9166 was evaluated on different aspects of the operant self-administration behavior. In this study, we found that the intracerebroventricular infusion of LSP2-9166 dose dependently reduced ethanol consumption, motivation for ethanol and reacquisition of ethanol self-administration after abstinence. Together, these results support recent preclinical findings showing that pharmacological modulation of mGlu receptors may serve as an effective treatment for reducing ethanol consumption and relapse. Highlights: LSP2-9166 reduced ethanol operant self-administration. LSP2-9166 reduced motivation to self-administer ethanol. LSP2-9166 reduced reacquisition after a period of abstinence. LSP2-9166 did not change sucrose operant self-administration. These data confirm the interest of targeting mGlu4/mGlu7 in alcohol use disorder.